Force Majeure: Impact on the Occupation Level of the Hospitality Industry in Palu City - Meldawati, Lucyani; Mustamin, Mustamin; Afdalia, Nadhira; Betty, Betty; Yuniar, Latifah Sukmawati; Erwinsyah, Erwinsyah; Gunarsa, Arif; Putra, Yosua Angkasa (Jurnal Ilmiah Akuntansi Kesatuan, 2025)
The hospitality industry in Palu City experienced rapid growth until it was abruptly disrupted by two major force majeure events: a series of natural disasters in 2018 and the global coronavirus pandemic beginning in 2020. These events caused significant physical and economic damage, particularly to star-rated hotels. This study aims to examine the impact of force majeure on hotel occupancy rates in Palu City, focusing on the periods preceding, during, and following both crises. Using a descriptive comparative method, the research analyzed data collected through interviews, observation, and documentation from ten selected star-rated hotels in Palu City. Quantitative data were supported by visual figures and tables that showed changes in hotel units, room availability, and occupancy levels over several years. The results indicate a sharp decline in hotel operations after each event, followed by a gradual recovery during the new normal period. Occupancy rates dropped as low as 15 per cent in 2020 but rebounded to 70–80 per cent in 2021. The study concludes that while the hospitality sector in Palu is highly vulnerable to external shocks, it also demonstrates resilience through adaptation and recovery strategies.